64a3 – 1
⟹ (4a)3 – (1)3
Using the formula (a3 + b3) = (a – b) (a2 + ab + b2)
Here a = 4a and b = 1.
⟹ (4a – 1) (16a2 + 4a + 1)
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
RELATED QUESTIONS :